2013
DOI: 10.1111/bju.12159
|View full text |Cite
|
Sign up to set email alerts
|

Treatment efficacy and outcomes using a third generation shockwave lithotripter

Abstract: Objectives• To evaluate the clinical efficiency of a third generation electromagnetic shock wave lithotripter, the Lithoskop ® (Siemens, Erlangen, Germany), regarding outcomes, stone disintegration, retreatment and complication rates.• To compare the results of the Lithoskop with other currently available systems and the reference standard lithotripter, the HM-3 (Dornier MedTech Europe GmbH, Wessling, Germany). Patients and Methods• We analysed the data from 183 patients, including 13 children, undergoing extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 35 publications
(78 reference statements)
3
9
0
2
Order By: Relevance
“…SFRs (64.2 %) at 1 week after SWL were comparable to those of previous studies on UC (52-90 %) [2,17,18]. Secondary outcomes evaluated were also similar between the two groups, and both groups had acceptable complication rates.…”
Section: Discussionsupporting
confidence: 82%
“…SFRs (64.2 %) at 1 week after SWL were comparable to those of previous studies on UC (52-90 %) [2,17,18]. Secondary outcomes evaluated were also similar between the two groups, and both groups had acceptable complication rates.…”
Section: Discussionsupporting
confidence: 82%
“…The probability of renal stone clearance after ESWL decreased with increasing stone size in all locations (14, 16). Tan et al reported a SF rate of 53% and a CS rate of 81% at three-month follow-up for the ESWL treatment of 1,666 renal stones.…”
Section: Discussionmentioning
confidence: 93%
“…Renal tissue injury, haemorrhage and left out residual stone fragments are other related complications [6,72,97] . Recently a third generation electromagnetic shock wave lithotripter, the Lithoskop ® was introduced which was found to be associated with fewer complications as compared to the existing lithotripters [99] .…”
Section: Extracorporeal Shock Wave Lithotripsymentioning
confidence: 99%